Trademark or patent? The effects of market concentration, customer type and venture capital financing on start-ups' initial IP applications. Issue 4 (19th May 2017) - De Vries, Geertjan; Pennings, Enrico; Block, Joern H.; Fisch, Christian
Abstract: We analyse the initial IP applications of 4, 703 start-ups in the U.S., distinguishing between trademark and patent applications. Our empirical results show that start-ups are more likely to file for trademarks instead of patents when entering markets with a higher market concentration. Furthermore, we find that start-ups that are primarily active in business-to-consumer markets instead of business-to-business markets are more likely to file trademarks. Finally, the involvement of a venture capitalist (VC) affects the initial IP application. VC-backed start-ups are more likely than other start-ups to file initial IP in the form of trademarks rather than patents. This paper contributes to research on the use of IP rights in start-ups and to the literature on new venture strategy.